Panax ginseng Total Protein Facilitates Recovery from Dexamethasone-Induced Muscle Atrophy through the Activation of Glucose Consumption in C2C12 Myotubes. (6th August 2019) - Jiang, Rui; Wang, Manying; Shi, Lei; Zhou, Jingyuan; Ma, Rui; Feng, Kai; Chen, Xuenan; Xu, Xiaohao; Li, Xiangyan; Li, Tong; Sun, Liwei
Abstract : Background. The clinical anti-inflammatory drug dexamethasone (DEX) can cause many side effects such as muscle atrophy for long-term use. Muscle atrophy induced by DEX may be caused by decrease of glucose consumption. Panax ginseng C.A. Meyer was previously considered to be an antiatrophic agent for glucocorticoid- (GC-) treated therapies. As one of the main components, it remains unclear whether ginseng total protein (GP) facilitates recovery from muscle atrophy induced by DEX. Methods. In this study, GP was extracted and purified with Sephadex-G50. C2C12 myoblasts was induced with 2% horse serum to differentiate into C2C12 myotubes. Cell viability was analyzed by the MTT assay, and Ca 2+ concentration was analyzed by a flow cytometer. The release of lactic dehydrogenase (LDH) and the glucose consumption were analyzed by spectrophotometry. The phosphorylation of AMP-activated protein kinase (AMPK), phosphoinositide 3-kinase (PI3K), and protein kinase B (Akt) and the expression of glucose transporter 4 (GLUT4) were analyzed by Western blotting. The phosphorylation of AS160 was quantified by Immunofluorescence staining. Results. We found that GP increased cell viability and increased myotube diameter in high-dose DEX-treated C2C12 myotubes for 24 h, but this activity was not found in the enzymatic hydrolyzed GP group. GP reduced muscle atrophy by decreasing the expression of key proteins such as muscle RING-finger protein-1 and muscle atrophy F-box, reducing the Ca 2+ concentration, and decreasing the release of LDH in DEX-injured C2C12 myotubes. Moreover, GP improved glucose consumption and increased the phosphorylation of AMPK, PI3K, Akt, and AS160 and the expression of GLUT4 in DEX-treated C2C12 myotubes. Conclusion. The results of this study suggest that GP has effects on recovering DEX-induced muscle atrophy and cell injury, which may improve glucose consumption via the AMPK and PI3K/Akt pathways in high-dose DEX-treated C2C12 myotubes. This study provides in vitro mechanistic insights into the recovery of muscle atrophy with GP treatment.